Entrenamiento mental en una cantera del fútbol profesional Colombiano (2020)
Introduction: It is increasingly necessary to train the mental aspect in high performance and mainly in the lower categories of soccer. For this, the theory of sports psychology and organizational psychology are taken into account to make a diagnosis and, subsequently, a mental training program aimed at achieving the objectives. Main Objective: Implement a mental training plan that contributes to the achieve of the sports goals of the CLUB X lower divisions in the sub13 and sub-17 categories, win the Ponysoccer tournament for the sub-13 category and win the National tournament for the sub17 category. Population: The project was carried out with two soccer teams with around 20 athletes, each one, who belonged to the sub-13 and sub-17 categories of the CLUB X youth team. Methodology: A mental training program was proposed that implement during the 2019 season generating training to improve psychological skills in sport. Results: Improvements were obtained in concentration, greater awareness was gained in communication for teamwork, the impact of emotional sensitivity on athletes was improved and the objective of the sub-13 category was met, but not that of the U17 category. Conclusions: Despite the best skills obtained from mental training, performance sport can vary a lot during the season, so it is necessary to adjust the goals as new adversities appear or as the planning for the beginning of the year changes.